Chemical fingerprint of robusta coffee beans from various local clones in Tanggamus, Lampung Province, Indonesia - ALVI YANI; MURHADI MURHADI; SUBEKI SUBEKI; TANTO. P. UTOMO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Yani A, Murhadi, Subeki, Utomo TP. 2025. Chemical fingerprint of robusta coffee beans from various local clones in Tanggamus, Lampung Province, Indonesia. Biodiversitas 26: 2222-2234. This research was conducted to analyze the chemical composition of dry-processed green coffee beans from several local?robusta clones, namely Randu Alas, Kasio, Komari, Kopi Hijau, and Kopi Kuning. The study was held from May to August 2024 in Way Harong Village, Lampung Province, Indonesia, with analysis done in two laboratories. The analysis included defect values, coffee quality, moisture content, yield, and density based on the Indonesian National Standard (SNI). The study was designed using a Completely Randomized Design with five treatments and three replications. Chemical fingerprints were identified using UPLC-MS/MS and MassLynx software. The results showed defect values of 14.15-29.15 (grades 2-3), yields of 19.30-21.16% (highest in Kopi Hijau and Komari), moisture content of 7.79-11.34% (lowest in Kopi Kuning), and density of 601.66-605.66 g/cm³. The chemical compositions were consistent up to Rt 7.38 minutes but varied beyond this point, with 18 compounds in Randu Alas, 20 in Kasio, 19 in Komari, 15 in Kopi Hijau, and 18 in Kopi Kuning. Overall, 10 major compounds were identified, including caffeine, chlorogenic acid, 4-aminobenzoic acid, trans-zeatin, umbelliferone, hymecromone, cynarine, (3aR,4R,5R,7aR)-4-(4-Hydroxy-3-methoxyphenyl)-1-oxo-7-[(2R,3R)-3,5,7-trihydroxy-4-oxo-3,4-dihydro-2H-chromen-2-yl]-1,3,3a,4,5,7a-hexahydro-2-benzofuran-5-carboxylic acid, benzyl 2-methyl-4-(4-nitrophenyl)-6-oxo-1,4,5,6-tetrahydro-3-pyridine carboxylate and Methyl (1R,3R)-1-(1,3-benzodioxol-5-yl)-2,3,4,9-tetrahydro-1H-?-carboline-3-carboxylate.